The Urgency of Leniency Program Against Cartels in Indonesia: Lesson Learned from Singapore Competition Law - Reni Budi Setianingrum; Muhammad Hawin (Jurnal Media Hukum, 2022)
Globalization is characterized by a process where the economy becomes more tightly integrated and manifested in the form of free trade. Free trade forced by economic globalization has brought adverse effects. Some of the harmful effects of free trade include the rise of international cartels, for instance, those involved in price-fixing, bid-rigging, output limitation, and market sharing. This normative legal research aims to examine the application of leniency programs in the enforcement of Competition Law in Singapore and how Indonesia can learn from Singapore. The research indicates that one particular method is commonly used in several countries in the context of law enforcement against cartels, which is known as the leniency program or the Whistleblower. Singapore, as one of the neighboring countries of Indonesia, also applies for the leniency program. As a result, Singapore has successfully resolved many international cartel issues. Consequently, the leniency program gives benefits for providing evidence for related cases. In conclusion, Indonesia should learn from Singapore's experience in implementing the leniency program to prevent the negative effect of free trade, including the proliferating international cartels.